Analizar la importancia de las medidas compensatorias en la comunidad de kasiwolin por el proyecto eólico jepirachi de las empresas públicas de Medellín. (2021)
The present research aims to analyze the importance of compensatory measures in the community of kasiwolin, municipality of Uribía, the Colombian Guajira, for this process we worked methodologically with a descriptive approach research typical of the qualitative framework where two instruments such as observation are implemented and the interview with a group of ten indigenous people of different roles within the kasiwolin community.